Influence of extracellular polymeric substances on membrane fouling and cleaning in a submerged membrane bioreactor - Nuengjamnong, C; Kweon, JH; Cho, J; Ahn, KH; Polprasert, C (MAIK NAUKA/INTERPERIODICA, 2005)
There is little information available on the correlation between the concentration of extracellular polymeric substances (EPS) and membrane fouling as well as cleaning efficiency. In this study, two lab-scale flat submerged membrane bioreactors (SMBRs at sludge retention times (SRTs) of 25 and 250 days were operated at a constant permeate flux (12.5 1 m(-2) h(-1)). Samples of activated sludge were tested to quantify the concentration of extractable EPS using cation exchange resin. Batch filtration tests were also performed to determine the specific cake resistances and the flux recoveries. The extractable EPS and protein concentrations were relatively low at the prolonged SRT, leading to cake layers easily removable by the physical manual cleaning or the de-ionized water backwashing and the chemical cleaning with sodium hypochlorite methods. The extent of flux recoveries (both in SMBRs and batch filtration tests) and macroscopic as well as microscopic images indicated that the chemical cleaning could enhance the effectiveness of cleaning. The membrane fouling and cleaning mechanisms were also discussed.
Keywords: ACTIVATED-SLUDGE; WASTE-WATER; MICROFILTRATION; FILTRATION; ULTRAFILTRATION; MODEL